Ocean equity: from assessment to action to improve social equity in ocean governance - Bennett, Nathan J.; Relano, Veronica; Roumbedakis, Katina; Blythe, Jessica; Andrachuk, Mark; Claudet, Joachim; Dawson, Neil; Gill, David; Lazzari, Natali; Mahajan, Shauna L.; Muhl, Ella-Kari; Riechers, Maraja; et al. (Frontiers in Marine Science, 2025)
Inequity is ubiquitous in the ocean, and social equity receives insufficient attention in ocean governance and management efforts. Thus, we assert that proponents of sustainability must center social equity in future ocean governance, to address past social and environmental injustices, to align with international law and conservation policy, and to realize objectives of sustainability. This obligation applies across all marine policy realms, including marine conservation, fisheries management, climate adaptation and the ocean economy, in all socio-political contexts and at different geographical scales. Indeed, many governmental, non-governmental, and philanthropic organizations are striving to advance social equity across their ocean sustainability focused agendas, policies, programs, initiatives, and portfolios. To date, however, there has been limited attention to how to meaningfully assess status and monitor progress on social equity in ocean governance (aka “ocean equity”) across different marine policy realms. Here, we contribute to ongoing efforts to advance ocean equity through providing guidance on five steps to develop bespoke, fit to purpose and contextually appropriate assessment and monitoring frameworks and approaches to measure status of and track changes in ocean equity. These steps include: 1) Clearly articulating the overarching purpose and aim; 2) Convening a participatory group and process to co-design the assessment framework; 3) Identifying important objectives, aspects and attributes of social equity to assess; 4) Selecting and developing indicators, methods, and measures; and 5) Collecting, analyzing and evaluating data. Then, we discuss four subsequent steps to take into account to ensure that assessments lead to adaptations or transformations to improve ocean equity. These steps include: 1) Communicating results to reach key audiences, to enable learning and inform decision-making; 2) Deliberating on actions and selecting interventions to improve ocean equity; 3) Ensuring actions to improve ocean equity are implemented; and, 4) Committing to continual cycles of monitoring, evaluation, learning and adapting at regular intervals. Following these steps could contribute to a change in how oceans are governed. The diligent pursuit of ocean equity will help to ensure that the course towards a sustainable ocean is more representative, inclusive and just.